Please solve for x
Factor out x-1.
... (x-1)(1 + x) = 3(x-1)
... (x-1)(x +1 -3) = 0 . . . . subtract the right side
... (x -1)(x -2) = 0 . . . . . . simplify
... x = 1 . . . or . . . x = 2 . . . . use the zero-product rule*
_____
* A product is only zero when one or more of its factors is zero.
x-1+x(x-1)=3(x-1)
x^2-1=3x-3
x^2-3x+2=0
Factor: (x-1)(x-2)=0
Set factors equal to 0:
x-1=0 and x-2=0
x=1 or x=2
True
False
Step-by-step explanation:
y=-9 paralel x-axis
True
y=-9↓↓
x----------------------------
-9--------------------------